Politique et imagination féminine dans Natures Pictures de Margaret Cavendish (1656) - Claire Boulard-Jouslin (Etudes Epistémè)
In 1656, Margaret Cavendish publishes a puzzling book entitled Natures Pictures drawn by Fancies Pencils to the Life, which gathers in eleven books numerous prefaces, poetry in verse and prose, fables as well as novellas, romances and lastly her own biographical account. Natures Pictures, as the title suggests, offers the reader a contradictory and disconcerting text, as it promises a book that will search for natural truth both in a scientific and an imaginary way. It thus uses two concepts that were getting increasingly antagonistic in the 17th century. Our aim will therefore be to show that Margaret Cavendish refuses to reduce this opposition between imagination and science to that of facts and fiction. By resorting to a variety of literary genres and by turning contradiction into a system she thus offers the reader an alternative to Baconian empiricism as well as to Aristotelism. However it seems that Natures Pictures is more than a book of controversy on the new scientific methods. It is also by its themes and its structure clearly a political act of resistance against the Cromwellian regime. Margaret Cavendish, a royalist exile in Antwerp, hides an anti-republican propaganda behind a seemingly incoherent scientific and literary creation. She thus uses fancy as a tool to subvert the notion of scientific truth. She also points to the reader the noblest way to (her own) political truth. The aesthetics of fragmentation, of atomization and paradox that is inscribed in the very structure of the book then becomes the key. Read in its multiple (literary, biographical, scientific and political) perspectives Natures Pictures is in fact a coherent, spiritual as well as baroque anamorphotic portrait of Margaret Cavendish herself.